Estudio técnico para el desarrollo de un sistema que permita controlar el servicio de pedidos y entregas de bebidas, para la distribuidora “Big Daniel”, ubicada en el sector La Chorrera, en la ciudad de Babahoyo - Baquerizo Sarcos, Alex (2021)
The purpose of this case study is to develop a beverage order and delivery service control system for the distributor "Big Daniel", located in the La Chorrera sector, in the city of Babahoyo, which aims to streamline the processes that are carried out manually on a daily basis and with inconveniences, this system will help these processes to be more efficient and with greater security of the information that can be collected, either from the workers or the staff in general who work in this distributor. The system that will be used in this distributor will obtain less loss of products and money, it will also be able to generate trust towards the customers to whom it is distributed since in a computerized way there is a way to know the delivery dates of products and the orders thereof with the personnel in charge of it, so much so that it is a way to schedule the orders that are generated to the distributor to make their respective deliveries with the products that customers request in a safe way.